2000
DOI: 10.1046/j.1524-475x.2000.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase production in regenerating axolotl spinal cord

Abstract: In urodele amphibian spinal cord regeneration, the ependymal cells lining the central canal remodel the lesion site to favor axonal regrowth. We profiled the production of matrix metalloproteinases by injury-reactive mesenchymal ependymal cells in vivo and in vitro and found that matrix metalloproteinases are involved in this remodeling process in the axolotl (Ambystoma mexicanum). The production of cell-associated matrix metalloproteinases in vivo was shown to be identical to that in our cultured ependymal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
3
37
0
1
Order By: Relevance
“…The MRL/MpJ mouse has a heightened and prolonged local expression of MMPs, including both MMP-2 and MMP-9, following ear punch or after injury to the cortex or retina in the CNS (Gourevitch et al, 2003; Hampton et al, 2004; Tucker et al, 2008). MMPs are important mediators of tissue regeneration in urodeles (Chernoff et al, 2000; Monaghan et al, 2007), yet their functions after injury in the mammalian CNS are complex. MMP-9 is upregulated at 1–2 days after SCI, during the period of neutrophil recruitment and tissue degradation (Noble et al, 2002; Goussev et al, 2003; Fleming et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The MRL/MpJ mouse has a heightened and prolonged local expression of MMPs, including both MMP-2 and MMP-9, following ear punch or after injury to the cortex or retina in the CNS (Gourevitch et al, 2003; Hampton et al, 2004; Tucker et al, 2008). MMPs are important mediators of tissue regeneration in urodeles (Chernoff et al, 2000; Monaghan et al, 2007), yet their functions after injury in the mammalian CNS are complex. MMP-9 is upregulated at 1–2 days after SCI, during the period of neutrophil recruitment and tissue degradation (Noble et al, 2002; Goussev et al, 2003; Fleming et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that MMPs facilitate axonal regeneration in the mammalian PNS (Heine et al, 2004; Kobayashi et al, 2008; Shubayev and Myers, 2004; Zuo et al, 1998), and the CNS of lower vertebrates (Chernoff et al, 2000). Researchers also found that increased MMP expression after mammalian CNS injury is correlated with areas of increased axonal outgrowth and the subsequent enhancement of functional recovery (Ahmed et al, 2005; Duchossoy et al, 2001; Hsu et al, 2006).…”
Section: Harnessing Proteases To Promote Neural Regenerationmentioning
confidence: 99%
“…After initial stage of trauma, when cell death, axon damage and demyelination are taking place, the glial scar starts developing [5,75]. Following, the production of ECM molecules increases at the damage [76,77]. Then activation and migration to the damage site of microglia occur, where they serve microphage function, particularly by removing disturbed myelin [78].…”
Section: а Bmentioning
confidence: 99%